Imaging the Heterogeneity of the Oxygen Evolution Reaction on Gold Electrodes Operando: Activity is Highly Local - Zwaschka, Gregor (ACS Catal, 2020)
[Image: see text] Understanding the mechanism of the oxygen evolution reaction (OER), the oxidative half of electrolytic water splitting, has proven challenging. Perhaps the largest hurdle has been gaining experimental insight into the active site of the electrocatalyst used to facilitate this chemistry. Decades of study have clarified that a range of transition-metal oxides have particularly high catalytic activity for the OER. Unfortunately, for virtually all of these materials, metal oxidation and the OER occur at similar potentials. As a result, catalyst surface topography and electronic structure are expected to continuously evolve under reactive conditions. Gaining experimental insight into the OER mechanism on such materials thus requires a tool that allows spatially resolved characterization of the OER activity. In this study, we overcome this formidable experimental challenge using second harmonic microscopy and electrochemical methods to characterize the spatial heterogeneity of OER activity on polycrystalline Au working electrodes. At moderately anodic potentials, we find that the OER activity of the electrode is dominated by <1% of the surface area and that there are two types of active sites. The first is observed at potentials positive of the OER onset and is stable under potential cycling (and thus presumably extends multiple layers into the bulk gold electrode). The second occurs at potentials negative of the OER onset and is removed by potential cycling (suggesting that it involves a structural motif only 1–2 Au layers deep). This type of active site is most easily understood as the catalytically active species (hydrous oxide) in the so-called incipient hydrous oxide/adatom mediator model of electrocatalysis. Combining the ability we demonstrate here to characterize the spatial heterogeneity of OER activity with a systematic program of electrode surface structural modification offers the possibility of creating a generation of OER electrocatalysts with unusually high activity.